An Investigation of the Impact of Dual Careers on Athletes’ Short-Term and Long-Term Financial Security - Amollo, William Motto (Πανεπιστήμιο Πελοποννήσου, 2024)
In the realm of sports science, a dual career involves a combination whereby an athlete participates in a particular sport competitively, while simultaneously pursuing an alternative profession or education. Dual career has been widely studied, and researchers have found it to be a phenomenon that ultimately benefits athletes in their quest to secure their future in various domains, including financial freedom, increased social network, and employment opportunities. The present study seeks to investigate how dual career impacts financial security in the short term and the long run, using the Kenya Rugby Union national team players as the case study. The study integrated a mixed methods qualitative study technique that includes both secondary and primary data. The finding indicates that a dual career, although challenging, positively impacts financial security to a great extent. It has also been established that education plays a pivotal role in fostering dual career development among athletes, support structures beyond personal development contribute to the overall financial well-being of players and that career duration and transition planning also enhance a person’s financial situation in the long term.
Keywords: Επαγγελματικός αθλητισμός - Κοινωνικές απόψεις; Επαγγελματικός αθλητισμός - Κένυα; Επαγγελματική αποκατάσταση - Κένυα; Ράγκμπι; Professional sports - Social aspects; Professional sports - Kenya; Vocational rehabilitation - Kenya; Rugby football; Dual career; Financial security; Kenya Rugby Union (KRU)